The relationship between fat mass, cardiovascular fitness and physical self-description among male children / Adlin Adnan - Adnan, Adlin (2014)
The ongoing epidemic of obesity in children has highlighted the importance of body fatness for health and its consequences for childhood physical self-description. The purpose of this study was to determine the correlation between fat mass, cardiovascular fitness and physical self-description among male children aged 10-12 years old. One hundred and fifty six school children were involved. The participants were 16% underweight, 46% normal weight, 13% overweight and 24% obese. Fat mass (FM) was measured by taking triceps and subscapular skinfold thickness, cardiovascular fitness (CVF) was measured using six-minute walk test (6MWT) and physical self-description was measured using Physical Self Description Questionnaire (PSDQ). Average distance walked differ from each BMI group (underweight 643±77 m ; normal weight 616±81 m ; overweight 622±101 m and obese children 597±73 m). This study found that FM does not have any relationship with cardiovascular fitness. Overall physical self-description does not significantly related with fat mass but had significant relationship with cardiovascular fitness. This shows that Malaysian urban children were more concern about their cardiovascular fitness and less attention were paid towards their physical self description.